Upaya Peningkatan Nilai Ekonomi Teh Salak di Kelurahan Karang Joang KM.21 dengan Product Branding dan Digital Marketing - Anggela, Anggela; Prayitno , Budi; Puspita , Anggela; Inayah , Anindya Putri; Definawati, Khairun Amalia; Syafatullah , M. Aqsal Ilham; Muhyiddin , M. Naufal; Jehana , Oktaviani Agnesia; Putri , Yulia Al Zahrah (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
One of the three pillars of higher education (Tri Dharma Perguruan Tinggi) is community service. One way to realize this principle is through participation in the PMMD (Student Community Service Program). This program aims to enable students to apply the knowledge gained at the university to benefit the surrounding community. This particular community service project was motivated by the potential of